2007
DOI: 10.1007/s10681-007-9481-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity evolution through participatory maize breeding in Portugal

Abstract: Natural, and in particular, artificial (human) selection may pose a danger to the existing crop genetic diversity. Nevertheless, on-farm breeding systems seem to achieve phenotypic improvements even though preserving variability. Using SSR markers, we analysed several selection cycles, over a 20 years period, of a Portuguese on-farm participatory maize OPV-'Pigarro' breeding project. No significant differences in allelic richness (N ar ), observed heterozygosity (H O ), expected heterozygosity (or gene diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
2
24
0
1
Order By: Relevance
“…On the contrary, ear length decreased significantly [38]. Molecular SSR mark-er data, from [42], on three selection cycles (C0-1984, C9-1993 and C20-2004), revealed that no effective loss of genetic diversity has occurred during the selective adaptation to the farmer's needs and the regional growing conditions. Variation among selection cycles represented only 7% of the total molecular variation, indicating that a great proportion of the genetic diversity is maintained in each selection cycle.…”
Section: Breeding Outputmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, ear length decreased significantly [38]. Molecular SSR mark-er data, from [42], on three selection cycles (C0-1984, C9-1993 and C20-2004), revealed that no effective loss of genetic diversity has occurred during the selective adaptation to the farmer's needs and the regional growing conditions. Variation among selection cycles represented only 7% of the total molecular variation, indicating that a great proportion of the genetic diversity is maintained in each selection cycle.…”
Section: Breeding Outputmentioning
confidence: 99%
“…Genetic diversity has not been reduced from the "Pigarro" bred before 1984 to those examples improved after 2004, but the genetic diversity maintained is not exactly the same. Mass selection seems to be an effective way to conserve diversity on-farm, and interesting phenotypic improvements were achieved as the bigger ears farmers' objective [42].…”
Section: Breeding Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, results can be found on the evolution of farmer varieties based on genetic markers, for instance [11][12][13], but there are few results based on phenotypic traits that are of direct relevance to the farmers [12,14]. Thus, in the EU, research programme Farm Seed Opportunities [15], experiments over three years studied on-farm cultivation and selection in contrasting environments of farmer varieties of wheat, maize, bean and spinach.…”
Section: Legislation Issuesmentioning
confidence: 99%
“…The number of alleles is often compared within and among studies to investigate which populations or groups of populations shows a higher diversity (Flajoulot et al 2005;Sardaro et al 2008;Patto et al 2008). The coefficient of variation of number of alleles was decisively reduced when comparing subsamples with 40 genotypes to 10 genotypes but a moderate decrease was still observed between 40 and 20 genotypes (Table 1).…”
Section: Resultsmentioning
confidence: 99%